The grasshopper - Loves, June (Nelson Australia South Melbourne, 1994)
A story of a carefree grasshopper who spends his summer singing and playing, while a diligent ant works hard to gather food for the winter. When winter arrives, the grasshopper finds himself unprepared and struggles to survive, while the ant is well-fed and cozy.